Pengaruh Kualitas Produk Dan Lokasi Terhadap Keputusan Pembelian (Studi Kasus Pada Konsumen Kafe Kopi Tuku Dukuh Atas, Jakarta Pusat) - Rousdy Safari Tamba; Ananda Putri Febrianti (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.This study aims to analyze the influence of product quality and location on purchasing decisions at TukuDukuh Atas Coffee Shop, Central Jakarta. The method used is quantitative research with data collectiontechniques through questionnaires to 100 respondents who have purchased products at Tuku Coffee Shop.The sample was taken using non-probability sampling techniques. Data processing was conducted usingIBM SPSS Statistics version 30.0 and analyzed through multiple linear regression. The results of the studyindicated that product quality (X1) and location (X2) have a positive and significant effect on purchasingdecisions (Y), with t-values of 10.475 and 3.672, respectively. Partially, product quality has a 72.4%influence on purchasing decisions, while location has a 48.3% influence. The simultaneous test (F-test)showed that both variables together significantly influence purchasing decisions with an F-value of 151.525,a significance level of 0.001 (less than 0.05), and a coefficient of determination (R²) of 0.758. These resultsindicated that 75.8% of the variation in purchasing decisions can be explained by product quality andlocation.Keywords: Sustainable Attitude, Perfectionist Attitude, Social Recommendation